Atributos físicos, químicos e estoques de carbono e nitrogênio do solo sob diferentes sistemas de uso e manejo na mesorregião central mineiro - Igor Costa de Freitas (2016)
This study aimed to evaluate the physical and chemical attributes, and contents and stocks of carbon and nitrogen in a typical dystrophic Red Latosol after one year of conversion of degraded pasture into systems of Integrated Crop-Livestock-Forest (ICLF) and forage cropping in Curvelo (MG). Soil samples were collected from depths of 0-5, 5-10, 10-20 and 20-30 cm in the following treatments: ICLF areas with eucalyptus intercropped with corn and marandu grass (ICLF M), corn and java (Macrotyloma axillare) (ICLF J), and corn, mandaru grass and java (ICLF J + M); areas with monoculture of marandu grass (MAR) and java (JAVA); marandu intercropped with java (J + M), and pasture in degradation process (PAST). The contents and stocks of C and N of soil in areas of ICLF M, MAR, PAST and native vegetation (NV) of Cerradão were measured. The following physical attributes were assessed: soil density (SD) and particle density (PD), total porosity (TP), geometric mean diameter (GMG) and weighted mean diameter (WMD), and aggregate stability index (ASI); and the chemical ones: soil organic matter (SOM), phosphorus (mehlich-1), pH (active acidity), sum of bases (SB), effective cation exchange capacity (ECEC) and potential cation exchange capacity (PCEC), and base saturation (BS). Soil organic matter (SOM) dynamics was evaluated through the following attributes: total organic C (TOC), and total N (TN); stock of TOC (CStock) and TN (NStock); organic C (OC) in free light fractions (FLF), sand (F-sand), and silt + clay (F-silt + clay) from MOS. For each variable, the mean and the confidence interval were calculated by using Student's t-test (p <0.05), and for SOM quality parameters a hierarchical grouping analysis was performed. The soil physical attributes presented few modifications due to the short time (one year) of implementation of the systems of use and management evaluated. As for the chemical attributes, in general, there was improvement in soil quality under ICLF systems expressed by increased values of SOM, phosphorus, PCEC and BS. The conversion of low productivity pasture into ICLF M system promoted the recovery of CStocks to levels close to those obtained in NV at 0-30 cm depth. For NStock, no significant changes were observed in the study period. It was also observed an increase in OC contents of FLF of the soil under ICLF M system, presenting values similar to those obtained in NV up to 20 cm depth. MAR system presented values of TOC, TN, CStock, NStock and OC in FLF higher than those observed in PAST. Due to lack of adequate management in PAST system, loss of a more stable fraction of SOM (F-silt + clay) was also observed. It was noted from the cluster analysis of ICLF M, MAR, PAST and NV treatments that there was similarity between MAR and PAST systems, whereas ICLF M system presented improvements in SOM quality, with better similarity to NV. Thus, it is concluded that there is a need for continuous studies to verify possible improvements in soil quality provided by the implementation of ICLF system over time.